Hostage diplomacy and illiberal states: analysing the factors driving hostage diplomacy in illiberal states - Law, Marcus Wai Kiat (Nanyang Technological University, 2023)
As hostage diplomacy poses a direct violation of international law and norms, it seems improbable for it to gain traction as an acceptable form of diplomatic activity. However, it has had an ostensible recent resurgence, leading to an increased number of accusations from western nations, and the international community denouncing the state weaponization of human hostages to achieve their foreign policy objectives. Notably, such instances are highly isolated and specific to some illiberal states. The question remains, why do some illiberal states employ hostage diplomacy against other states? By conducting a multiple case study analysis on Turkey’s 2016 Hostage Diplomacy, Iran’s 1979 Hostage Crisis, and China’s 1967 Hostage Crisis, this paper identifies three factors that explains why illiberal states engage in hostage diplomacy; namely, for bargaining leverage, the pursuit of narrow domestic interests, and the logic of tit-for-tat. This paper adds to the literature on hostage diplomacy by exploring the factors that motivate illiberal states to conduct hostage diplomacy against other states.